A Feasibility Study on the Implementation of Automated AIS and their Impacts on Financial Reporting at Kingstons Ltd - Induna, Anesu M (Midlands State University, 2017)
This research overall aim was to determine if it was feasible to implement automated accounting information systems and determine impacts implementation might have on quality financial reporting at Kingstons. Since it has been evident that Kingstons limited has been struggling to invest in its operations for the past 5 years due to financing difficulties the researcher resorted to an investigation which tried to determine if lease financing was appropriate for Kingstons ltd. The research adopted use of quantitative research methods in carrying out the study. Quantitative methods were adopted when measurement of variables and verification of existing theories was required. Numbers and statistics enhanced the ability to verify quantitative data. During the research it was noted that the following challenges have been factors contributing to the failure of implementing the system at Kingstons ltd. Costs, technical complexity, lack of management support and lack of systems knowledge. These challenges were reviewed in literature and employee’s responses to research questions also reviewed that these were evident at the company and have contributed to the company’s failure. An investigation on the use of lease financing as financing alternative for Kingstons ltd was made. Research showed that most of the respondents to interview questions and questionnaires, vehemently affirmed that lease financing and the chief reason being reduced burden on cash flows. This factor was confirmed by (Kiisel, 2013) who also had the opinion that cashflow is not tied up when lease financing is used compared to when a cash purchase is done. A determination of whether a relationship between computerized AIS and quality reporting exists was done in the research. Findings showed that timeliness and accuracy are enhanced and confirmation was through literature and mainly from responses to questionnaires and interview questions. The research shall help management at Kingstons ltd to identify areas where they are lacking most and devise methods to circumvent them. The research can thus be used for reference sake and as a guideline.